METHODS OF SYNTHESIS ENERGY SUPPLY ELECTIC ENGINE UNMANNED AERIAL VEHICLE - Казак, В.; Горбач, О. (Science-based technologies, 2011)
Direct  current  motors  main  types  are  considered.  The analysis  of  the  main  methods  of  control  DC  motors is held. The basic relations used in the direct current motor management are showing. The methods of speed control  motor  as  the  drive screws  main  component  of  unmanned  aerial  vehicles  are analyzed.  Calculations  of  the solar cell parameters as a source of propulsion power unmanned aerial vehicle are given.